2022
DOI: 10.3390/agronomy12102317
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Nitrogen Source in Regulating Lignin Biosynthesis, Storage Root Development and Yield of Sweet Potato

Abstract: The understanding of the effects of nitrogen sources on lignin synthesis in sweet potato during storage root formation is limited. In this study, we investigated the effects of different nitrogen source on sweet potato storage root formation and development, as well as lignin synthesis in potential storage roots. The sweet potato cultivars Shangshu 19 and Jixu 23 were used in field experiments in 2019 and 2020. Three treatments were tested: (a) no nitrogen fertilizer application (control); (b) 60 kg hm−2 ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The upregulation of starch biosynthesis and downregulation of lignin biosynthesis in potential storage roots are the main events during the storage root formation period [ 8 , 15 , 22 ], probably because the activity of carbon flow towards carbohydrate metabolism is stronger than the delivery into phenylpropanoid biosynthesis during the storage root formation period [ 14 , 30 ]. Previous findings have shown that low sucrose and high hexose content in the root system could facilitate storage root formation [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The upregulation of starch biosynthesis and downregulation of lignin biosynthesis in potential storage roots are the main events during the storage root formation period [ 8 , 15 , 22 ], probably because the activity of carbon flow towards carbohydrate metabolism is stronger than the delivery into phenylpropanoid biosynthesis during the storage root formation period [ 14 , 30 ]. Previous findings have shown that low sucrose and high hexose content in the root system could facilitate storage root formation [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose is decomposed into hexoses by the SuSy and sucrose invertase pathways, and the former is the main source for fructose and UDP-glucose biosynthesis, which provides the substrate for starch biosynthesis [ 14 , 31 ]. Crop root development is adversely correlated with lignin deposition, and lignin accumulation has a negative effect on root development [ 8 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations